Essentials of children's literature - Lynch-Brown, Carol (Pearson, 2011)
Clear, concise, direct narrative that combines lists, examples, figures, and tables with prose make this brief, affordable, straightforward book the perfect guide to sharing literature with children in the classroom. Written by a well-respected author team, this resource is ideal for pre-service and in-service teachers alike, and much appreciated for its wealth of hands-on suggestions and ideas. Selective, up-to-date lists of recommended books are conveniently organized by sub-genre; multicultural and international children's literature is integrated throughout; and an up-dated color insert features recent illustrations from picture books (including examples of computer-generated art) and graphic novels.